Evolution of endemismon a young tropical mountain - Isa, Ipor (International Weekly Journal of Science, 2015)
Tropical mountains are hot spots of biodiversity and endemism1–3, but the evolutionary origins of their unique biotas are poorly understood4. In varying degrees, local and regional extinction, long-distance colonization, and local recruitment may all contribute to the exceptional character of these communities5. Also, it is debated whether mountain endemics mostly originate from local lowland taxa, or from lineages that reach the mountain by longrange dispersal from cool localities elsewhere6. Here we investigate the evolutionary routes to endemism by sampling an entire tropical mountain biota on the 4,095-metre-high Mount Kinabalu in Sabah, East Malaysia. We discover that most of its unique biodiversity is younger than the mountain itself (6 million years), and comprises a mix of immigrant pre-adapted lineages and descendants from local lowland ancestors, although substantial shifts from lower to higher vegetation zones in this latter group were rare. These insights could improve forecasts of the likelihood of extinction and ‘evolutionary rescue’7 in montane biodiversity hot spots under climate change scenarios.